Stefano Calabrese, Retorica e scienze neurocognitive (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2014)
Recensiamo Calabrese, Stefano. Retorica e scienze neurocognitive. Roma: Carocci, 2013. Stampa.